2017
DOI: 10.1093/conphys/cox013
|View full text |Cite
|
Sign up to set email alerts
|

Obtaining accurate glucose measurements from wild animals under field conditions: comparing a hand held glucometer with a standard laboratory technique in grey seals

Abstract: Hand-held point-of-care devices are increasingly used in wildlife settings because they are simple, portable, cheap and use small amounts of blood. However, our data show low accuracy of a glucose meter across different ages and physiological states in grey seals. Glucometers need rigorous testing before use in wildlife species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…Validation assays have been done in many groups (e.g. fish, Beecham et al , 2006; Ball and Weber, 2017; mammals, Bennett et al , 2017; birds, Lieske et al , 2002), but none have evaluated the real applicability of such technology in invertebrates. From the works that have used glucose meters in crustaceans (Lorenzon et al , 2004, 2008; Butcher et al , 2012; Aliko et al , 2015), none have tested their usability or validated the method prior to use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Validation assays have been done in many groups (e.g. fish, Beecham et al , 2006; Ball and Weber, 2017; mammals, Bennett et al , 2017; birds, Lieske et al , 2002), but none have evaluated the real applicability of such technology in invertebrates. From the works that have used glucose meters in crustaceans (Lorenzon et al , 2004, 2008; Butcher et al , 2012; Aliko et al , 2015), none have tested their usability or validated the method prior to use.…”
Section: Discussionmentioning
confidence: 99%
“…Although a well-established method, its use in the field is impractical as it demands several equipment and materials that are heavy, delicate and expensive (Stoot et al , 2014). Recently, there has been an increase in the use of point-of-care (POC) devices, primarily designed for human health, on animal physiology (Brown et al , 2008; Awruch et al , 2011; Andrewartha et al , 2016; Bennett et al , 2017). POC devices are portable, easy to use and generally cheaper than well-established lab techniques.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Harter et al (2015) confirmed that the i-STAT portable clinical analyser was able to obtain accurate measures of blood pH in the sandbar shark ( Carcharhinus plumbeus ), but could not reliably indicate partial pressure of oxygen or haemoglobin oxygen saturation measurements. Likewise, when Bennett et al (2017) compared laboratory testing of blood glucose with measurements obtained from a portable glucometer in wild grey seals ( Halichoerus grypus ), they found the glucometer to be highly precise, but not accurate. While these validations indicate true limitations for use in some species, there are circumstances where adjustments can be made to allow for biologically accurate results.…”
Section: Where Are Researchers Placing Emphasis For Tool Development?mentioning
confidence: 99%
“…Glucose is the most abundant monosaccharide in vertebrates and is a vital metabolic fuel that provides tissues with energy when oxidized [4]. Blood glucose concentrations are regulated by a delicate balance of mechanisms involving hormones, glucose uptake, and oxidation [5,6]. In reptiles, blood glucose variations can occur due to alterations in metabolic rate, physiological changes, and environmental factors [7].…”
Section: Introductionmentioning
confidence: 99%